Current knowledge of targeted-release budesonide in immunoglobulin A nephropathy: A comprehensive review - Liao, Jian; Zhou, Yijing; Xu, Xiuqin; Huang, Ke; Chen, Pengtao; Wu, Yuhao; Jin, Biao; Hu, Qianlong; Chen, Guanlin; Zhao, Shankun (Frontiers in Immunology, 2023)
Immunoglobulin A (IgA) nephropathy is a common autoimmune kidney disease. Accumulating studies showed that IgA nephropathy may be partially correlated with mucosal immune system dysfunction. Systemic corticosteroid treatment exerts an essential protective effect against renal deterioration in IgA nephropathy. However, long-term use corticosteroids may cause systemic side effects. The novel targeted-release formulation (TRF) of budesonide has been shown to deliver the drug to the distal ileum with the aim of minimizing the adverse events for patients with IgA nephropathy. In this review, we have summarized all the current evidence of the effects of TRF-budesonide protecting against IgA nephropathy. Three randomized controlled trials (RCTs), two case reports, and an ongoing Phase 3 trial (NCT03643965), were under comprehensive review. These included studies demonstrated that TRF-budesonide could remarkably reduce proteinuria, hematuria, and creatinine, as well as preserve renal function. The local immunosuppressive effects exhibited by TRF-budesonide may represent a novel and promising approach to treating IgA nephropathy. However, the current evidence was only derived from limited trials. Therefore, more well-designed RCTs are still warranted to validate the curable profile of TRF-budesonide in treating IgA nephropathy.